Posterior Urethral Valves; Outcome Analysis after Endoscopic Valve Ablation - Kumar Sah, Sanjay; Prasad Chaudhary, Ramanandan; Silwal, Shirish (Annapurna Journal of Health Sciences, 2023)
Introduction: Posterior urethral valves, a major male infra-vesical obstructive uropathy leading to chronic renal failure are most common paediatric urological emergencies with an incidence of 1:5000 -1:8000. Early diagnosis, management and follow up of these patients is challenging in low socio-economic countries like Nepal. This study evaluates the cases with posterior urethral valves and their outcomes after endoscopic valve ablation over a period of five years. Methods: In this five year retrospective study from January 2016 to December 2020, all the cases with posterior urethral valves undergoing endoscopic valve ablation were reviewed and data were analysed for age, presentation, diagnosis and outcome at follow-up after management. Results: A total of sixty patients with posterior urethral valves were managed with definitive endoscopic ablation in the five year period. Median age at ablation was 11 months (10 days to 4 years). Commonest presentation was features of bladder outlet obstruction evident by poor stream, straining and dribbling of urine. Only 26.7% cases were managed in neonatal period due to low suspicion of valve in prenatal fetal scan. 83.3% of patients had complete relief from obstruction with normal urinary stream at follow up after ablation of valves with 15% of cases needing re-ablation of the residual valve. Two cases had to undergo anti-reflux surgery two years after valve ablation. Mortality was seen in one case due to cross sepsis. Majority of patients were in regular follow-up which showed its direct relationship to the outcome of the disease after valve ablation. Conclusion: Early detection, proper relief of obstruction and regular follow-up strategies can avoid life threatening complications of posterior urethral valves. Only treating posterior urethral valves is not the aim of obtaining successful relief of obstruction. Parent’s education, developing prenatal ultrasound skills to detect or suspect prenatal PUVs and early referral to tertiary centers where these patients can be managed promptly are equally important.